Genetic and physical characterization of recombinant plasmids associated with cell aggregation and high-frequency conjugal transfer in Streptococcus lactis ML3. - Anderson, D G (1984)
Restriction mapping was employed to characterize the 104-kilobase (kb) cointegrate lactose plasmids from 15 independent transconjugants derived from Streptococcus lactis ML3 as well as the 55-kb lactose plasmid ( pSK08 ) and a previously uncharacterized 48.4-kb plasmid ( pRS01 ) from S. lactis ML3. The data revealed that the 104-kb plasmids were cointegrates of pSK08 and pRS01 and were structurally distinct. The replicon fusion event occurred within adjacent 13.8- or 7.3-kb PvuII fragments of pSK08 and interrupted apparently random regions of pRS01 . Correlation of the transconjugants' clumping and conjugal transfer capabilities with the interrupted region of pRS01 identified pRS01 regions coding for these properties. In the 104-kb plasmids, the pRS01 region was present in both orientations with respect to the pSK08 region. The replicon fusion occurred in recombination-deficient (Rec-) strains and appeared to introduce a 0.8 to 1.0-kb segment of DNA within the junction fragments. The degeneration of the cointegrate plasmids was monitored by examining the lactose plasmids from nonclumping derivatives of clumping transconjugants. These plasmids displayed either precise or imprecise excision of pRS01 sequences or had dramatically reduced copy numbers. Both alterations occurred by rec-independent mechanisms. Alterations of a transconjugant 's clumping phenotype also occurred by rec-independent inversion of a 4.3-kb KpnI-PvuII fragment within the pRS01 sequences of the cointegrate plasmid.